METHODOLOGY FOR IMPROVING STUDENTS' DELPHI CRITICAL TECHNOLOGIES AND CREATIVE COMPETENCIES - Komiljon Muminov (The Bioscan, 2024)
This article is intended for students studying at the bachelor's degree program of the Pedagogical Higher Education Institution. Pedagogical conditions and quality indicators of using innovative organizational and didactic forms of education in methodically equipping students with knowledge of creative pedagogical competence, information and didactic support are described. The method of improvement of students' creative competences based on Forsayt technologies, innovative approach is covered.